The Therapeutic Mechanisms of Shenyan Oral Liquid I Against Chronic Kidney Disease Based on Network Pharmacology and Experimental Validation - Cheng, Xudong; Liang, Guoqiang; Liu, Min; Song, Rujun; Zhou, Lan; Ren, Yan; Huang, Yuyu; Jin, Weimin; Jiang, Chunbo (Combinatorial Chemistry & High Throughput Screening, 2024)
Background Chronic Kidney Disease (CKD) leads to structural and functional abnormalities of the kidneys and seriously jeopardizes human health. Shenyan Oral Liquid (SOLI), a Chinese medicinal preparation, has been reported to protect podocytes in patients with chronic kidney disease (CKD). Objective The objective of this study is to investigate the mechanism of action of the Chinese medicinal preparation Senyan Oral Liquid (SOLI) in the treatment of CKD by protecting podocytes through network pharmacology technology and experimental validation. Methods Compounds of SOLI and targets of CKD disease were collected and screened. The SOLI network of bioactive compounds targeting CKD and the protein-protein interaction (PPI) network were constructed using Cytoscape software and the STRING online database. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses were performed using the R software Cluster Profiler package. Molecular docking was performed using Autodock software to verify the binding ability of bioactive compounds and target genes. Subsequently, the potential mechanism of SOLI on CKD predicted by network pharmacological analysis was experimentally studied and verified in an adriamycin-induced nephropathy rat model. Results A total of 81 targets of SOLI components acting on CKD were identified. The results of the PPI analysis clarified that five key target genes (TNF, AKT1, IL6, VEGFA, and TP53) play a critical role in the treatment of CKD by SOLI. The GO analysis and KEGG enrichment analysis indicated that SOLI acts through multiple pathways, including the PI3K/AKT signaling pathway against CKD. Molecular docking showed that the main compounds of SOLI and five key genes had strong binding affinity. In a rat model of adriamycin-induced nephropathy, SOLI significantly ameliorated disease symptoms and improved renal histopathology. Mechanistic studies showed that SOLI upregulated the expression level of Nephrin, inhibited the PI3K/AKT pathway in renal tissues, and ultimately suppressed the activation of autophagy-related proteins in CKD. Conclusion SOLI exerted a renoprotective effect by regulating the Nephrin-PI3K/AKT autophagy signaling pathway, and these findings provide new ideas for the development of SOLI-based therapeutic approaches for CKD.
Keywords: PI3K/AKT signaling